Cato the Censor and the Beginnings of Latin Prose : From Poetic Translation to Elite Transcription - Sciarrino, Enrica, 1968- (Book collections on Project MUSE., 2011)
"Through a methodologically innovative exploration of the interlacing of genre and form with practice, Enrica Sciarrino bridges the gap between these two scholarly camps and develops new areas of inquiry by rescuing from the margins of scholarship the earliest remnants of Latin prose associated with Cato the Censor--a "new man" and one of the most influential politicians of his day. By systematically analyzing poetic and prose texts in relation to one another and to diverse authorial subjectivities, 'Cato the Censor and the Beginnings of Latin Prose: From Poetic Translation to Elite Transcription' offers an entirely new perspective on the formation of Latin literature, challenges current assumptions about Roman cultural hierarchies, and sheds light on the social value attributed to different types of writing practices in mid-Republican Rome"--Publisher's description